1995
DOI: 10.1002/1097-0142(19950701)76:1<4::aid-cncr2820760103>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory neuroblastoma. An immunohistochemical, ultrastructural, and flow cytometric study

Abstract: Background. Olfactory neuroblastoma is an uncommon neuroectodermal tumor of the upper nasal cavity, microscopic features of which are not always homogeneous. No morphologic features have been found to correlate reliably with prognosis. Methods. Twenty‐six olfactory neuroblastomas occurring in 14 females and 12 males, ages 18–78 years, were studied by immunohistochemistry, electron microscopy, and DNA flow cytometry. Survival rates were statistically analyzed relative to several variables. Results. Microscopica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
1
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 40 publications
5
68
1
3
Order By: Relevance
“…In conclusion our case represents the first demonstration of a ''dot-like'' cytokeratin expression in an ONB, a feature hitherto undescribed to our knowledge and supplements the Literature data [2][3][4][5]. Pathologists should be aware of this potential diagnostic pitfall in distinguishing a high grade ONB from a high grade NEC, particularly in scanty & Martina Mandarano mandaranomartina@gmail.com biopsies [2], in which is crucial an integration of immunohistochemical data with careful interpretation of morphological features.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In conclusion our case represents the first demonstration of a ''dot-like'' cytokeratin expression in an ONB, a feature hitherto undescribed to our knowledge and supplements the Literature data [2][3][4][5]. Pathologists should be aware of this potential diagnostic pitfall in distinguishing a high grade ONB from a high grade NEC, particularly in scanty & Martina Mandarano mandaranomartina@gmail.com biopsies [2], in which is crucial an integration of immunohistochemical data with careful interpretation of morphological features.…”
supporting
confidence: 74%
“…In their paper entitled ''Neuroendocrine Neoplasm of the Sinonasal Tract: Neuroendocrine Carcinomas and Olfactory Neuroblastoma'' Shah and Perez-Ordoñez [2] reported a cytokeratins positivity, observed in up to 30 % of ONBs, in accordance with other Authors who documented cytokeratins expression from 23 to 35 % of cases, both focal or diffuse with strongly intensity, but never showing a paranuclear or globoid stain (''dot-like'' pattern). This latter being an important difference respect to Neuroendocrine Carcinoma (NEC) [1][2][3][4][5]. Furthermore another recent article by Holbrook et al [6] demonstrated that cytokeratin 18 (CK18) was positive in ONB separating tumor cells into nests.…”
mentioning
confidence: 99%
“…Contrary, mutations of TP53 were not found in any of 19 cases of ONB, but about the half of all cases showed p53 overexpression [37]. Another study revealed p53 aberrant expression in 16 out of 26 cases (62%) [38]. Nevertheless, recent studies have identified point mutations of TP53 in two cases of metastatic ONB [39, 40].…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…The limitation of their study was uneventful disease course amongst sample as the majority of patients did not show any recurrence and a small cohort size. Longer survival may be associated with an increased abundance of S-100 protein-positive cells and a low Ki-67 labeling index [38], and this may probably be associated with differentiation, as the number of sustentacular cells decreases with increased tumor grade.…”
Section: Prognostic and Predictive Factorsmentioning
confidence: 99%
See 1 more Smart Citation